Action Experience and Action Discovery in Medicated Individuals with Parkinson’s Disease - Bednark, Jeffery G.; Reynolds, John N. J.; Stafford, Tom; Redgrave, Peter; Franz, Elizabeth A. (Frontiers in Human Neuroscience, 2016)
Parkinson’s disease (PD) is a neurodegenerative disorder that markedly affects voluntary action. While regular dopamine treatment can help restore motor function, dopamine also influences cognitive portions of the action system. Previous studies have demonstrated that dopamine medication boosts action-effect associations, which are crucial for the discovery of new voluntary actions. In the present study, we investigated whether neural processes involved in the discovery of new actions are altered in PD participants on regular dopamine treatment, compared to healthy age-match controls. We recorded brain electroencephalography (EEG) activity while PD patients and age-matched controls performed action discovery and action control tasks. We found that the novelty P3, a component normally present when there is uncertainty about the occurrence of the sensory effect, was enhanced in PD patients. However, action discovery was maintained in PD patients, and the novelty P3 demonstrated normal learning-related reductions. Crucially, we found that in PD patients the causal association between an action and its resulting sensory outcome did not modulate the amplitude of the feedback correct-related positivity (fCRP), an EEG component sensitive to the association between an action and its resulting effect. Collectively, these preliminary results suggest that the formation of long-term action-outcome representations may be maintained in PD patients on regular dopamine treatment, but the initial experience of action-effect association may be affected.